Pricing strategies in a dual-channel green supply chain with cannibalizationand risk aversion - Syed Asif Raza; Srikrishna Madhumohan Govindaluri (Operations Research Perspectives, 2019)
This paper investigates a dual-channel supply chain in which a single manufacturer offers the standard product through a direct online channel and an inaugural green product through a traditional physical store (regular) channel. The manufacturer invests in a greening effort to produce green products by incorporating environment friendly features. These green products are offered to customers at a higher price in coordination with a downstream retailer. Standard (non-green) products, however, do not possess the enhanced green features and are offered by the manufacturer at a discounted price to customers using a direct channel. In this paper, we develop dual-channel supply chain (DCSC) coordination models for a more generalized case where the manufacturer and retailer are assumed to be risk averse. The risk aversion is modeled using a popular measure, namely, the mean-variance criterion. Further, the proposed DCSC coordination models enhance the existing DCSC coordination models in the literature, by allowing varying proportions of the market share associated with the traditional regular and online channels in lieu of fixed proportions. This is achieved by utilizing the price differentiation tool from revenue management for effectively segmenting the proportion of expected market share of the regular and online channels as a variable instead of a fixed value. In the proposed model for decentralized channel coordination, the manufacturer decision variables include price differentiation, wholesale price for greening products, and pricing in the direct channel along with the greening effort investment. Unlike manufacturer, the retailer plays the role of the follower within a leader-follower framework and decides on the retail price of the green products sold through the regular channel. For the integrated channel, the manufacturer determines the pricing for green and standard products in addition to the greening effort in a monopoly. The study also explores the supply chain coordination under revenue- and cost-sharing contracts for the dual channel supply chain. The models are unique since they capture the effects of demand cannibalization or demand leakage, which affects the supply chain revenue maximization due to price differentiation. A detailed numerical experimentation is carried out to investigate the impact of the risk-aversion, demand leakage, and market uncertainty on the performance of supply chain coordination.
Keywords: 330; Supply chain; Greening; Pricing; Market segmentation; Environment; Cannibalization; Risk aversion; Mean-variance analysis